Na melhor idade - mulheres, sexualidades e envelhecimentos: um estudo etnográfico a partir de bailes de terceira idade - Bortolotti, Lige Mara Rauber (2010)
Sexuality of elderly people is nowadays an authentic object of studies which has been expanding under different theoretical and disciplinary approaches. In order to contribute to this field we carried out a qualitative ethnographic research to understand how sexuality and aging are related during aging period of women who frequent third age balls in the city of Santa Maria, Rio Grande do Sul, Brazil. As theoretical reference we used authors from social sciences such as Clifford Geertz, Michel Bozon, Anthony Giddens, Pierre Bourdieu, as well as studies of gender and sexuality from Judith Butler, Guacira Louro and Richard Miskolci and also theoretical conceptions by Michel Foucault in the field of sexuality, power and discourse. At first, the study focused the participant observation in balls from the central region of the city. Then we interviewed women who participated in these events. From the data collected from observations, interviews and theory, we described the events and the interviews and discussed issues pointed by the researcher. We noticed that sexuality occupies a privileged place in the constitution of these women at the best age as subjects of an ideal type of healthy and active aging. From the interviews we noticed that sexuality in the discursive level was surrounded by worries related to the male performance and to corporal and physical issues mainly genital ones. Due to heteronormativity the sexual intercourse with men are privileged mainly with younger men without the need of an affective relationship apart from the sex. The socialization with the peers and the relationships established from the balls showed important things in the elaboration of individual life projects in which sexual practice also showed as in indicative of health and inclusion at what they call best age .